The comic and musical theater in the First Republic: The presence of Afro-Brazilian culture in the city of Rio de Janeiro (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
This article aims to bring up some problematizations about the presence of comic and musical theater during the First Republic, its historical perspectives and memories, but, above all, a whole set of clashes and depreciations promoted by elites of the period exactly because this theater is a popular artistic representation, of success, contrary to the intellectual interests of the time and manifestly representative of Afro-Brazilian culture in Rio soil.
Keywords: Comic and musical theater; Rio de Janeiro; Tiradentes Square; Resistance